Perchlorate, iodine and the thyroid - Leung, Angela M. (2010)
In pharmacologic doses, perchlorate inhibits thyroidal iodine uptake and subsequently decreases thyroid hormone production. Although pharmacologic doses may be used in the treatment of hyperthyroidism, recent literature has focussed on the detection of low levels of perchlorate in the environment, groundwater and foodstuffs and their potential adverse effects on human thyroid function. This is of particular concern to the developing foetus and infant, whose normal neurodevelopment depends on adequate iodine intake for the production of thyroid hormones. Further research is needed to clarify the potential health effects of low-level chronic environmental perchlorate exposure. The health impact of environmental perchlorate may be dependent upon adequate iodine intake and should be interpreted in combination with other environmental exposures that are also potential thyroidal endocrine disruptors.